Educative Values of Peace Mind Mysticism of Sunan Bonang In the view of Islam - Fatchullah Zarkasi (International Journal of Emerging Issues in Early Childhood Education, 2019)
The majority of Javanese which many called "abangan" has its own perspective on the major religions in the world. For Niels Mulder in his book, the Javanese tend to view Islam as a religion is Arab, so that Islam seemed to fizzle placed as the basis of life for the Javanese belief. However, virtually no Muslims in Indonesia who have never heard the name Wali Songo, collective unit 9 guardian. Sunan Kalijaga better known than all eight other guardians with various famous work. Puppet world is said to be the work of these guardians, as sekaten, which has been called, is a tradition of the Prophet's birth day celebration that is celebrated officially the Kingdom of Yogyakarta and Surakarta, until today. Sidi Gazalbarevealed that: "Value is something that is abstract. Value is not a concrete object, not a fact, not just a question of right and wrong that demands empirical evidence, but rather a matter of appreciation that is desired, liked and disliked.While Educative education comes from the word that means pendidikan.Sedangkan education question in this case is the Islamic education. So according to Prof. Dr. Omar M. Taomy al Pendidikaan Syaibany in his philosophy of Islam, it can be concluded that: "Islamic Education is an attempt to change the behavior of individuals in the life of their community and also in the surrounding environment through the education process. The changes are based on the values of Islam.”DOI: http://doi.org/10.31098/ijeiece.v1i2.32